2023
DOI: 10.1021/acsami.3c02466
|View full text |Cite
|
Sign up to set email alerts
|

Toolbox of Advanced Atomic Layer Deposition Processes for Tailoring Large-Area MoS2 Thin Films at 150 °C

Abstract: Two-dimensional MoS2 is a promising material for applications, including electronics and electrocatalysis. However, scalable methods capable of depositing MoS2 at low temperatures are scarce. Herein, we present a toolbox of advanced plasma-enhanced atomic layer deposition (ALD) processes, producing wafer-scale polycrystalline MoS2 films of accurately controlled thickness. Our ALD processes are based on two individually controlled plasma exposures, one optimized for deposition and the other for modification. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
(136 reference statements)
1
3
0
Order By: Relevance
“…In both films, a significant amount of hydrogen is observed at 7.1 TFU (12–14%), which likely originates from the use of H 2 S plasma (which contains hydrogen radicals) in the preparation of the films, as has been reported before . Similar behavior was also observed in our recent work on the PEALD of MoS 2 . , In that work, we have shown that it is possible to mitigate H incorporation during PEALD by using advanced ALD supercycle approaches . Future studies will aim to minimize unintentional hydrogen content, thus enabling more stable resistivity values.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In both films, a significant amount of hydrogen is observed at 7.1 TFU (12–14%), which likely originates from the use of H 2 S plasma (which contains hydrogen radicals) in the preparation of the films, as has been reported before . Similar behavior was also observed in our recent work on the PEALD of MoS 2 . , In that work, we have shown that it is possible to mitigate H incorporation during PEALD by using advanced ALD supercycle approaches . Future studies will aim to minimize unintentional hydrogen content, thus enabling more stable resistivity values.…”
Section: Resultssupporting
confidence: 82%
“…7 Similar behavior was also observed in our recent work on the PEALD of MoS 2 . 46,47 In that work, we have shown that it is possible to mitigate H incorporation during PEALD by using advanced ALD supercycle approaches. 47 Future studies will aim to minimize unintentional hydrogen content, thus enabling more stable resistivity values.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in terms of the cost effectiveness and mass production, MOCVD and CVD methods are more suitable for industrialization than PLD and MBE. Additionally, benefiting from the layer-by-layer growth mode at low temperatures and high scalability, atomic layer deposition (ALD) is also a promising method for synthesizing large-area 2D materials with a uniform thickness. However, the 2D materials synthesized by ALD have lower crystallinity than samples synthesized by the other bottom-up deposition approaches mentioned above. Therefore, a subsequent high-temperature annealing process is generally preformed to improve crystallinity …”
Section: Advantages and Preparation Of 2d Semiconductorsmentioning
confidence: 99%
“…Regardless, most of the available ALD processes offer limited control over stoichiometry and crystallinity of MoS x . Plasma-enhanced ALD (PEALD) offers more freedom in tailoring film properties, which also enables control of HER performance. ,, Recently, we have shown that controlling the plasma chemistry via feed gas composition enables tailoring stoichiometry, crystallinity, morphology, and electronic properties of MoS x within a broad range …”
Section: Introductionmentioning
confidence: 99%